Dignity and patient-centred care for people with palliative care needs in the acute hospital setting: A systematic review. (September 2015) - Pringle, Jan; Johnston, Bridget; Buchanan, Deans
Background: A core concept behind patient-centred approaches is the need to treat people with, and preserve, dignity in care settings. People receiving palliative care are one group who may have particularly sensitive needs in terms of their condition, symptoms and life expectancy. Dignity is more likely to be violated in hospital settings. Given the high percentage of people with palliative care needs who are admitted to hospital during their last year of life, the provision of dignity enhancing and preserving care in that setting is of vital importance. Aim: To examine international evidence relating to dignity and person-centred care for people with palliative care needs in the acute hospital setting. Design: A systematic literature review was conducted, incorporating data extraction, analysis and quality appraisal of included papers. Data sources: MEDLINE, CINAHL, PsycINFO, ASSIA, EMBASE, Cochrane Database and Web of Science. Inclusion dates: 1 January 2000–1 April 2014. Eligibility criteria: Adult palliative care, acute care setting, dignity or person-centred care. Results: In all, 33 papers met the inclusion criteria for the review. Papers highlighted the many and varied potential threats to dignity for people with palliative care needs in acute settings, including symptom control and existential distress, approaches and models in care provision and healthcare settings and design. Conclusion: Acute hospital staff require adequate training, including symptom control, and the correct environment in which to deliver dignified and person-centred end-of-life care. Specific models/approaches to care can be beneficial, if adequate training regarding implementation is given. The needs of family members also require consideration, particularly following bereavement.